Impact of ovarian reserve markers on oocyte maturity and embryological outcomes in in vitro fertilization/intracytoplasmic sperm injection cycles: A retrospective cohort study - Soudabeh Sabetian; Fatemeh Dadgar; Zahra Esfandiari; Bahia Namavar Jahromi; Sareh Ashourzadeh; Somayyeh Safari; Sanaz Alaee (Clinical and Experimental Reproductive Medicine, 2026)
Objective: Despite advances in assisted reproductive technologies, predicting outcomes of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) remains difficult. Hormonal status, oocyte maturity, and ovarian reserve contribute to treatment variability. This study examined correlations among demographic, endocrine, and embryological parameters in women undergoing IVF and ICSI whose partners had normal semen profiles, and evaluated the effect of follicle-stimulating hormone (FSH) levels on outcomes.Methods: A retrospective analysis was performed on 488 women aged 18 to 45 years who underwent IVF and ICSI between 2022 and 2024. Data included age, body mass index (BMI), infertility duration, and levels of FSH, luteinizing hormone, anti-Müllerian hormone (AMH), thyroid-stimulating hormone, and fasting blood sugar. Embryological variables were oocyte yield, maturity stages (germinal vesicle, metaphase I, and metaphase II [MII]), and embryo count. Pearson correlations and the Kruskal–Wallis test were used to compare groups stratified by FSH (20 mIU/mL).Results: BMI and infertility duration showed weak correlations with embryological outcomes. AMH correlated positively with embryo count (r=0.29, p